(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Purpose: This study investigated motivational factors as correlates of librarians’ job satisfaction in libraries of two federal universities in South-South, Nigeria. The study sought to establish the nature and strength of the relationship between two selected motivational factors — training and development, and salary/wages — and the job satisfaction of librarians. Design/Methodology/Approach: A correlational research design was adopted for the study. The entire population of 60 librarians across the University of Calabar and the University of Benin constituted the study sample, using a census enumeration technique. Data were collected through a researcher-designed rating scale (RSMFCLIS) comprising 35 items rated on a four-point Likert scale. Mean scores, standard deviations, Pearson Product-Moment Correlation Coefficient, t-test statistics, and F-test multiple regression were used to answer the research questions and test the hypotheses at the 0.05 level of significance. Findings: Results revealed a significant positive relationship between training and development and librarians’ job satisfaction (r = .61, R² = 0.37; tcal = 9.68 > tcrit = 1.96, p < 0.05). A significant positive relationship was also found between salary/wages and librarians’ job satisfaction (r = .67, R² = 0.45; tcal = 11.34 > tcrit = 1.96, p < 0.05). Both null hypotheses were rejected. Salary/wages emerged as the stronger correlate, accounting for 45% of the variation in librarians’ job satisfaction. Implication: The findings imply that the adequacy of training and development opportunities and the timely disbursement of competitive salaries are critical determinants of librarians’ job satisfaction in federal university libraries. Where these motivational factors are inadequate, job dissatisfaction, declining service quality, and low morale are likely consequences, with negative implications for the academic mission of the university. Originality/Value: This study contributes to the limited body of literature on motivational factors and librarian job satisfaction specific to the South-South geopolitical zone of Nigeria. It provides empirical evidence and practical recommendations for university library management and policy makers on the motivational strategies most likely to improve the job satisfaction and performance of academic librarians.